Analysis of Profitability of Seshasayee Paper & Boards Limited (SPBL): A Case Study - Selvaraj, V.; Rajangam, P. (Indian Journal of Finance, 2013)
This paper aims to access the profitability position of SPBL from the year 2001-02 to 2010-11. To evaluate the profitability of the company, relevant ratios were used and statistical tools like mean, standard deviation, coefficient of variation, minimum, and maximum were applied, and to test the significant relationship between the relevant variables, the variables were tested with the help of correlation and regression analysis (t- test). In hypotheses testing, most of the hypothesis showed a statistically significant relationship between two variables. Hence, it was concluded that the overall performance of Seshasayee Paper&Boards Limited regarding profitability was sound during the study period, the company's market is growing, and it was earning an acceptable return on invested capital, and it has good future opportunities for growth.